Sejarah PLTA Lamajan Pangalengan Sebagai Situs Peninggalan Belanda di Kabupaten Bandung Tahun 1925 - Asri Nur Kholis Sofiah; Ajid Hakim (UIN Sunan Gunung Djati Bandung, 2020)
This study aims to determine how the history of the Lamajan Hydroelectric Power in 1925, both in terms of the geographical, demographic conditions of Pangalengan and also the components that still exist in Lamajan. Lamajan is a Dutch hydroelectric power plant (PLTA) which was built in 1924 in Pangalengan, Bandung and has been operating since 1925. Lamajan has three generator units, the engine used by Lamajan supplied from the Dutch factories Heemaf and Smit Slikkerveer, initiated by V.H Willem Smith & Co. and R.W.H. Hofstede Crull. The method used in this study is a qualitative method, namely by collecting data through literature and documentation. This method is carried out through four stages namely, heuristics, criticism, interpretation, and historiography. The results of this study show this hydroelectric power plant was built during the Dutch colonial era in 1920-1924 and operated in 1925. This power plant was initially built by a Dutch engineer named Willem Beyerinc K. for the electricity needs of sugar factories but over time was used to illuminate the area of Bandung and its surroundings, this power plant utilizes the flow of water from the Cisarua and Cisangkuy rivers.